2019
DOI: 10.1186/s12879-019-4229-3
|View full text |Cite
|
Sign up to set email alerts
|

A case report of HIV-1 superinfection in an HIV controller leading to loss of viremia control: a retrospective of 10 years of follow-up

Abstract: Background HIV controllers (HICs) are a rare group of HIV-1-infected individuals able to naturally control viral replication. Several studies have identified the occurrence of HIV dual infections in seropositive individuals leading to disease progression. In HICs, however, dual infections with divergent outcomes in pathogenesis have been described. Case presentation Here, we present a case report of a HIC diagnosed in late 1999 who displayed stable CD4 + … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
0
3
1
Order By: Relevance
“…Our results demonstrate the association between the presence of Env-EL9 immunodominant HLA-B*14:02-restricted CD8 + T-cell responses, viral evolution and immune escape with LVC. In contrast to other studies [ 29 31 ], the infection with two heterologous HIV-1 strains was not associated with LVC [ 20 , 24 , 32 ]. Our phylogenetic inferences describe viral evolution [ 5 ] and the potential contribution of variant emergence and replacement to LVC.…”
Section: Discussioncontrasting
confidence: 92%
“…Our results demonstrate the association between the presence of Env-EL9 immunodominant HLA-B*14:02-restricted CD8 + T-cell responses, viral evolution and immune escape with LVC. In contrast to other studies [ 29 31 ], the infection with two heterologous HIV-1 strains was not associated with LVC [ 20 , 24 , 32 ]. Our phylogenetic inferences describe viral evolution [ 5 ] and the potential contribution of variant emergence and replacement to LVC.…”
Section: Discussioncontrasting
confidence: 92%
“…Other studies retrospectively analysed cases identified through patients' abnormal laboratory values (e.g. increased VL, decreased CD4 counts, changed resistance patterns) [8,9,20], or using proviral DNA [21,34,35], which was not yet used to screen for superinfection. Also, available tools to investigate dual infections [30] are not yet tailored to identify superinfection, nor to work with individuals' longitudinal sequences.…”
Section: Discussionmentioning
confidence: 99%
“…The phenomenon of loss of control has been reported in studies of natural HIV-1 controllers, including elite controllers (ECs) and long-term nonprogressors (LTNPs) ( 10 , 11 , 37 40 ) aiming to delineate the biological correlates of spontaneous HIV-1 control. Nonetheless, it is currently unknown whether viremic nonprogressors (VNPs), a very rare phenotype characterized by a paradoxically nonpathogenic HIV-1 infection and sustained CD4 + T-cells counts despite continuous viral load, may eventually lose CD4 + homeostasis (LoH).…”
Section: Discussionmentioning
confidence: 99%